PRESCRIBING PATTERN OF ANTIEPILEPTIC DRUGS IN PEDIATRIC PATIENTS AT A TERTIARY CARE TEACHING HOSPITAL - KAUSHAL, PANCHAL; H, SHAH MEGHA; CHETNA K, DESAI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Epilepsy is one of the common neurological conditions worldwide. Methods: The observational, continuous, prospective, and single-center study was carried out to evaluate prescribing pattern of antiepileptic drugs (AEDs) in pediatric patients at a tertiary care teaching hospital of Gujarat for a total duration of 18 months. Patients were followed up monthly for the period of 3 months to evaluate seizure freedom, breakthrough seizure, and change in the AEDs, add-on therapy, treatment adherence and ADRs. Rationality was assessed for selection of drug and selection of the right dose according to recent guidelines. Results: Majority of patients in the age group of 7–9 years with mean age of 6.83 ± 3.09 years. Male-to-female ratio was 1.3:1. Total 73 AEDs were prescribed to pediatric epilepsy patients after diagnosis. Thirty-seven (69.80%) patients were prescribed AED on visit as monotherapy and 16 (30.20%) patients were prescribed polytherapy. Sodium valproate (77.36%) was most commonly prescribed AED followed by levetiracetam and carbamazepine. Most of AEDs were prescribed according to NICE guideline and by generic name. Conclusion: Conventional AEDs are still used as first line of treatment for pediatric epilepsy patients, although newer AEDs also frequently prescribed as add on or primary drug. Low birth weight, NICU admission, and non-compliance to treatment are associated with breakthrough seizures.